2020
DOI: 10.1093/mnras/staa3079
|View full text |Cite
|
Sign up to set email alerts
|

Models of distorted and evolving dark matter haloes

Abstract: We investigate the ability of basis function expansions to reproduce the evolution of a Milky Way-like dark matter halo, extracted from a cosmological zoom-in simulation. For each snapshot, the density of the halo is reduced to a basis function expansion, with interpolation used to recreate the evolution between snapshots. The angular variation of the halo density is described by spherical harmonics, and the radial variation either by biorthonormal basis functions adapted to handle truncated haloes or by splin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 96 publications
1
11
0
Order By: Relevance
“…On the other hand, they neglect any clumpiness, triaxility, twistedness and possible rotation of the halo. It has been recently demonstrated that high fidelity orbit reconstruction can be obtained by modelling the changing complex potential of a simulated isolated MW-mass galaxy using a multipole expansion at ∼100 Myr temporal resolution (Sanders et al 2020). The recent passage of a massive accreted satellite complicates the situation further due to the resonances induced in the central DM halo: large transient density and kinematic perturbations (Choi et al 2009) are produced, creating the classical 'conic' wake trailing the satellite (Chandrasekhar 1943) as well as a collective response to the system as a whole (Garavito-Camargo et al 2019) and leading to a temporary change in the concentration of the halo (Wang et al 2020).…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, they neglect any clumpiness, triaxility, twistedness and possible rotation of the halo. It has been recently demonstrated that high fidelity orbit reconstruction can be obtained by modelling the changing complex potential of a simulated isolated MW-mass galaxy using a multipole expansion at ∼100 Myr temporal resolution (Sanders et al 2020). The recent passage of a massive accreted satellite complicates the situation further due to the resonances induced in the central DM halo: large transient density and kinematic perturbations (Choi et al 2009) are produced, creating the classical 'conic' wake trailing the satellite (Chandrasekhar 1943) as well as a collective response to the system as a whole (Garavito-Camargo et al 2019) and leading to a temporary change in the concentration of the halo (Wang et al 2020).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This ensures that the centre of the MW-mass host is never more than 60 kpc away from the centre of the reference frame, allowing for great accuracy in our backward integrations in the adopted cylindrical coordinate system. We account for the fictious forces arising from our choice of the non-inertial reference frame (Sanders et al 2020). That is the total force on a test particle is…”
Section: Backward Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…To proceed forward, we follow Kalnajs (1977) who undertook a projection of all perturbed quantities onto a bi-orthogonal basis of potentials and densities. This practice gained a renewed interest in recent years (see, e.g., Garavito-Camargo et al 2021a;Sanders et al 2020) for its ability to solve the Poisson equation by construction, allowing for more natural reconstructions of the gravitational potential in simulations. In the context of linear response theory, this technique can also be used to solve the Poisson equation, while the CBE is transformed into an integral equation in a linear space.…”
Section: The Matrix Methodsmentioning
confidence: 99%
“…There exist a multitude of scenarios to explain the physical processes of the evolution of galaxies that reproduce well their observed properties. There are a number of papers (Gómez et al 2010;Correa et al 2015;Haghi et al 2015;Sanders et al 2020;Armstrong et al 2021) where various time-dependent model gravitational potentials based on cosmological models of the Universe were used to study the orbital history of Galactic objects. Only a change in the masses of the Galactic potential components are considered in some papers (see, e.g., Armstrong et al 2021); both a change in the masses and a change in the sizes of the components are considered in other papers (Gómez et al 2010;Haghi et al 2015).…”
Section: Introductionmentioning
confidence: 99%